PENGARUH PERMODALAN, AKTIVA PRODUKTIF DAN LIKUIDITAS TERHADAP PROFITABILITAS BANK RAKYAT INDONESIA SYARI’AH PERIODE 2010-2018 - Ahmad Mudzakir (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2019)
This research was conducted with the aim of examining the effect of capital, earning assets and liquidity on profitability at Syari'ah Bank Rakyat Indonesia. In its analysis capital is represented by the Capital Adequacy Ratio (CAR), earning assets are represented by Non Performing Financing (NPF), liquidity is represented by Financing to Deposit Ratio (FDR) and profitability is represented by Return On Equity (ROE). The data analysis technique used is multiple linear regression analysis. The results of this study indicate that partially CAR has a negative and significant effect on ROE, which means that capital has a positive and significant effect on profitability, then NPF has a negative and significant effect on ROE. profitability, then FDR has a positive and significant effect on ROE, which means that liquidity has a negative and significant effect on profitability. While simultaneously CAR, NPF and FDR have a significant effect on ROE, this means capital, earning assets and liquidity together have a significant effect on profitability.